The way of Schleiermacher’s modern religion and its enlightenment for Christianity and moral construction in modern China - ZHU, Yunfei (Journal of Research for Christianity in China (JRCC), 2025)
When Western civil society comes into being in the 18th century, the defects of its moral status are also increasingly exposed. From the religious point of view, Schleiermacher thinks that the root of moral defects lies in the fanatical and excessive pursuit of reason and interest, and suppressing religion. So Western civil society falls into “no science, no morals, no art, no love, no spirit, and really no letters”. Therefore, Schleiermacher argues that religion has an independent status, and sets the relationships between metaphysics, moral and religion.On the basis of this, Schleiermacher defines the essence of religion as intuition and feeling. He intend to take the feeling of absolutely depending which is brought by the intuiting universe as the core, and associate the finite and the infinite besides the human nature and the divine nature in order to enhance individual moral quality and social cohesion. At present, China is facing the transformation of modernity and the moral situations appear many new changes and problems. Schleiermacher’s religious thoughts will provide helpful enlightenment for Christianity and moral construction in modern construction.